Pengembangan Dressing Dolls Pada Stimulasi Kemampuan Toilet Training Di Taman Kanak-Kanak Gugus V Kecamatan Buleleng - Farah Attamimi; Putu aditya Antara (Universitas Pendidikan Ganesha, 2023)
Toilet training for toddler-aged children is an effort to train children to be able to control urination and defecation. On average, when children go to the toilet, they have difficulty removing their trousers or skirts. This research aims to train children to become independent, so they no longer ask other people for help when they want to go to the toilet. This research is development research with the model used, namely ADDIE. Data collection was carried out using a questionnaire-based Likert scale questionnaire. The instrument used to collect data was a questionnaire. The validity test of this assessment instrument is carried out through a content validity test (expert/expert test). The instrument developed will be tested by 2 media experts, 2 material experts, 3 teachers, and 5 children's responses. The data analysis technique uses qualitative and quantitative descriptive analysis. The research results, namely the results of validity analysis from media experts, obtained a score of 91.3%. The results of the validity of the material expert obtained a score of 97.1%. The teacher validity results obtained a score of 96.6%. The child's response test obtained a score of 96.3%. It was concluded that this research was